Antitrust as a panacea for economic development in Nigeria (2017)
Economic development aims at improving the wellbeing and quality of life of a community by creating and/or retaining jobs, supporting or growing incomes and the tax base. Free trade policies which create a high level of competition in the open market are necessary aids for economic development. On its part, Antitrust is a statutory and jurisprudential provision, through which public authorities preserve general welfare by preventing firms from limiting competition, creating monopolies, and charging excessive prices for their products. It aims to ensure the existence of competitive markets and guarantees that firms operating in the free market economy do not restrict or distort competition in a way to prevent the market from functioning optimally. From the foregoing, this paper examined the Nigerian antitrust regime and its import in the economic advancement of the Nigerian economy. The paper found that in developing countries including Nigeria, there is a paucity of antitrust legislation designed to protect consumers, promote free trade and commerce, and prevent unwholesome and unethical trade practices. With a well operated antitrust framework, Nigeria s economic growth will accelerate and gain better stability as well as increase consumer protection.